Pemanfaatan Whatsapp Group (WAG) pada Pembelajaran Jarak Jauh di Masa Pandemi Covid-19 - Puspito Aji (Proceedings Series on Social Sciences & Humanities, 2022)
The 21st century is a century of scientific development that is experiencing extraordinary acceleration so that the world of education must prepare itself to apply 21st century learning that integrates literacy skills, knowledge skills, skills and attitudes as well as mastery of technology. Teachers as agents of change in producing quality human resources as intelligent generations who have local wisdom that meets the demands of the character of 21st century, 4C students, namely communication, collaboration, critical thinking and problem solving, and creativity and innovation. The Covid-19 pandemic is one of the triggers for changing the education system in Indonesia, from the conventional way of learning in the classroom to switching to distance/online learning. Online learning requires the creativity and innovation of a teacher so that the transfer of knowledge and skills can work. In facing the industrial era 4.0, teachers must be able to upgrade themselves by developing their pedagogical competencies so that they are able to guide and direct students to be able to use their thinking and reasoning power well. In this pandemic period, time, location and distance become a big problem, so the implementation of learning requires the use of a media that can bridge the implementation of learning. From several existing digital media such as E-Learning, Google Classroom, Zoom Cloud Meeting, Google Meet, Whatsapp. The Whatsapp application is an application that can be chosen as an alternative learning media because it is very familiar among students, parents and the community. In addition, the WhatsApp application is very simple and easy to operate so that it becomes an application that is the favorite choice as a learning tool that is of interest to teachers and students from various levels of education, especially schools with lower middle social class backgrounds. The features provided are also quite diverse so that they can be used as learning support facilities, including sending text messages, sending photos and videos stored in the gallery or camera, sending office files in the form of word, excel, and powerpoint, calling, sending voice messages, doing video calls, share location using GPS. You can also use the WhatsApp application by creating a group called Whatsapp Group (WAG). Through WAG the teacher can send messages in the form of learning materials, so that after being sent, the teacher asks students to observe, discuss, ask questions, and do assignments from the presentation of the material presented.